2013
DOI: 10.1097/mpg.0b013e31829ce5cd
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Morbidity, and Treatment of Thrombosis in Children and Young Adults With Active Inflammatory Bowel Disease

Abstract: Pediatric inpatients hospitalized with IBD with colonic involvement have increased risk of TE, including complications of pulmonary embolism, recurrence, persistence, and indefinite long-term anticoagulation. Therapeutic anticoagulation in patients with IBD with active colitis appears safe. We identified both inherited thrombophilias and acquired risk factors in patients with IBD and TE. We presently use risk stratification and recommend prophylactic anticoagulation in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 19 publications
3
61
2
Order By: Relevance
“…Of the patients with a central line, 3.8% developed an associated venous thrombosis during the hospitalization. 28 The increased rates of venous thrombosis in the setting of IBD could be due to the high level of infl ammation at the time of line placement. Often these patients are admitted during an active IBD fl are or for surgery, leading to a period of increased inactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Of the patients with a central line, 3.8% developed an associated venous thrombosis during the hospitalization. 28 The increased rates of venous thrombosis in the setting of IBD could be due to the high level of infl ammation at the time of line placement. Often these patients are admitted during an active IBD fl are or for surgery, leading to a period of increased inactivity.…”
Section: Resultsmentioning
confidence: 99%
“…3 Risk of venothromboembolic events in pediatric inpatients with IBD colitis is also increased, although to a lesser extent than in adults, and such events are usually attributable to concurrent risk factors. 4 There is now a growing literature that patients with IBD are also at higher risk for arterial ischemic strokes. Singh et al 5 performed a meta-analysis of five large population studies and found that there was a modest increase in the risk of cerebrovascular dysfunction (defined as transient ischemic attack, ischemic and/or hemorrhagic stroke) in patients with IBD; the risk was higher in females than in males and in individuals younger than 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…A single-institution, retrospective review of hospitalized children and young adults with IBD showed increased risk, with an incidence of 1.9% for VTE among 532 patients aged 8 to 23 years. 23 A systematic review estimated a 4-to 20-fold increased risk in children with IBD compared to those without, with 60% occurring in the 12-to 18-year-old age-group. 24 Nylund and colleagues analyzed the triennial Healthcare Cost and Utilization Project Kids' Inpatient database across 5 time periods (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) and showed an RR of 2.36 (95% CI 2.15-2.58) for VTE in hospitalized children and adolescents with IBD.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%